Dampak Penggunaan Dan Analisa Pengaruh Styrofoam Sebagai Substitusi Pasir Dengan Bahan Tambah Plastiment-VZ Terhadap Nilai Kuat Tekan Beton - habib habib tamdullah (Jurnal Teknik Sipil dan Lingkungan, 2014)
As significant there are many major structure is usually at Indonesia, have a lot of done by research to concrete, and done by admixtures's increase to half and half concrete. On this research is made a mixed concrete planning styrofoam  without plus material and styrofoam's mixture concrete with added plastiment vz  from PT. Sika Indonesia, made using cement portland, base SK SNI 03-2834-1993. There is variation even mixture styrofoam  to half and half concrete is 0%, 25%, 50% and 75% for type second that concrete, with care condition up to 28 days are soaked. With object tests as cube fairish 15 cm x15 cm x15 cm. Of examination result, the greater substitution variation styrofoam  causing concrete weight becomes lighter until variation 75%. Meanwhile for strength to press, the most result optimal is substitution concrete s tyrofoam  with plus material plastiment vz  to K350 25% firmly presses 252,8 Kg / cm². In common substitution concrete styrofoam with plus material for each one concrete quality most turns in at medium strength concrete, and clas's concrete II. (concrete to structural).